Sensory quality of stored croissant-type bakery products. - B. Hozová; I. Kukurová; R. Turicová; L. Dodok (Czech Journal of Food Sciences, 2002)
The results are presented of the estimation of sensory quality (shape, odour, colour, taste, consistency, crust, crumb etc.), mould and yeast counts, aw value, and pH in 8 bakery croissant-type products with nougat cream filling during storage under laboratory conditions (20 ± 2°C) for the periods of up to 90 days (0; 30; 45; 60; 75 and 90 days). The products differed in the type of dough (brioche, croissant), the aw value of the cream, and in the presence or absence of sorbic acid in the spirit spray applied onto the surface of the products under investigation. The above-indicated parameters were examined also in the nougat cream samples on day 0 and 90 of the storage. The selected quality parameters permitted to estimate the shelf life of the products in the dependence on various technological conditions (sorbic acid, recipe, aw value).